MENSTIMULUS ASPEK SOSIAL MELALUI KEDISIPLINAN HIDUP SEHAT DENGAN PEMBELAJARAN DARING PADA ANAK USIA DINI - Cincin Sumayanti; Arifah A Riyanto; Ema Aprianti (IKIP Siliwangi, 2022)
Attention deficit hyperactivity disorder or ADHD is a disorder in a child who has difficulty paying attention or is known as hyperactivity. Children with ADHD in this study were motivated by the daily role of parents in accompanying children with the initials KPW. Condition of this child has obstacles to paying attention, high anxiety, and lack of concentration in various activities. While Sundanese is the mother tongue used by the West Java region. One of the methods used is singing to focus attention on ADHD children. This study aims to determine how the role of parents in stimulating Sundanese language skills with the singing method. This research method uses descriptive qualitative. Data collection techniques in this study used interviews, observations, and documentation. This study also uses qualitative data analysis, namely the process of systematically searching for compilers. The results of this study are successful because the role of great parents is to provide support in the form of emotional support and material support to children. When the researcher observed the parents accompanying the children in learning, patiently directing the children to follow the lesson, giving examples of Sundanese language by using the tone of the song that was exemplified by the teacher so that the child was able to do what was exemplified by the parents. The results of this study indicate that parents can stimulate the Sundanese language through the singing method.Anak merupakan makhluk sosial yang harus bisa menyelesaikan setiap permasalahan akibat dari interaksi dengan lingkungan sosialnya serta harus bisa menujukkan dirinya sesuai norma yang berlaku. Akibat dari tuntutan sosial tersebut maka anak harus mencapai kematangan sosial dan keterampilan pada aspek sosial. Peneliti menyadari bahwa aspek sosial ialah hal yang harus dipelajari sejak dini.Tujuan penelitian ini untuk menstimulus aspek sosial melalui kedisiplinan hidup sehat dengan cara melakukan pembiasaan sehari-hari seperti berinteraksi dengan orang tua di pagi hari, mandi sendiri, membereskan tempat tidur sendiri, dan makan sendiri. Metode penelitian menggunakan metode deskriptif kualitatif. Kelompok B usia 6 tahun sebanyak 10 anak menjadi subjek penelitian. Data diperoleh dari hasil wawancara, observasi, dokumentasi dan analisis data menggunakan reduksi, display dan menarik kesimpulan. Hasil penelitian menunjukkan bahwa dengan menstimulus aspek sosial anak usia dini melalui kedisiplinan hidup sehat dengan pembelajaran daring pada Kelompok B Di Kober Kadeudeuh mengalami peningkatan, dilihat dari hasil anak yang Berkembang Sangat Baik (BSB) pada Pertemuan ke-1 sekitar 2 sampai 3 anak berkembang meningkat hingga di Pertemuan ke-8 menjadi 6 hingga 7 anak berkembang meningkat.